Fiqh Gaya Hidup Global dalam Menyikapi Perubahan Sosial dan Tantangan Keagamaan Kontemporer - Khoirul Anwar; Nihayatut Tasliyah (LP2M Universitas Ibrahimy, 2025)
Globalization has become the ruler of the world that is ready to penetrate the public massively, both positively and negatively. The flow of globalization continues to flow to all corners of society by breaking down the boundaries of space and time. Whoever can control the global, then he will be the champion. Including in terms of lifestyle, such as fashion. For Muslims, through fiqh has claimed to be able to regulate all aspects of human behavior, let alone just fashion matters, Various schools of thought review their explanations at length. However, the global situation has divided three types of thinking, namely anti-modernity, influenced by modernity, and critical. Fiqh has formulated the concept of aurat as something that is principle or dharury, and basic (hajiyah) and provides a gap to complement the aspect of beauty or tahsiniy. Even so, the appearance in public space by showing the aspect of beauty or tahsiny actually contains a contestation between religion and global ideas, namely in terms of formulating fashion criteria, the struggle for artistic and religious identities, standardization of Islamic fashion, and hegemony. Through the choice of rationality, Muslims are free to outwit religion and follow market tastes.